Perawatan Internal Bleaching Menggunakan Teknik Walking Bleach Pada Gigi Insisif Sentral Kanan Rahang Atas (Case Report) - Rudy Djuanda (SONDE (Sound of Dentistry), 2019)
Tooth discoloration is defined as extrinsic or intrinsic staining based on localization and etiology, appearance, severity and adhesion to the tooth structure. Tooth discoloration is a cosmetic problem and the teeth whitening procedure is more conservative than the restorative method. Tooth discoloration, especially those treated endodontically is a matter of concern for patients and dentists. Among the various bleaching techniques, the technique of "walking bleach" with hydrogen peroxide stands out because of its superior aesthetic results with less side effects. This paper presents a case of tooth discoloration in non-vital teeth that was successfully bleached using the walking bleach method.